A niche in the Garbhagriha houses goddess Parvati - Mumbai Archive Project Team (Jio Institute, 2024)
A niche in the garbhagriha houses goddess Parvati, the embodiment of Shakti, the divine feminine power. Maha Shivaratri is a celebration of the divine union of Shiva and Shakti. Their relationship symbolizes the ideal marital bond and the balance of masculine and feminine energies in the universe.